Perchlorate Environmental Occurrence, Interactions and Treatment - Gu, Baohua; Coates, John D.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Perchlorate anion is a widespread, environmentally persistent contaminant recently discovered in U.S. groundwater and drinking water supplies that affect tens of millions of people. This book will summarize the most current knowledge and understandings of the extent of perchlorate contamination, chemical behavior, and recent development in innovative remediation technologies for perchlorate in the environment. Additionally, its natural occurrence and its unique isotopic signature (between natural and anthropogenic sources) and novel detection techniques are provided. The book is intended to provide the most comprehensive reference for environmental professionals, decision makers, geoscientists, university students and professors, and the general public. This book will provide a detailed description of the perchlorate chemistry and recent advances in innovative remediation technologies for perchlorate contamination and their pros and cons. Additionally, it will be the first book to describe the natural occurrence of perchlorate and its unique isotopic signatures for environmental forensics and its detection in the environment, particularly the real-time analysis using surface enhanced Raman spectroscopy.
Perchlorate: Challenges and Lessons -- The Chemistry of Perchlorate in the Environment -- Occurrence and Formation of Non-Anthropogenic Perchlorate -- Alternative Causes of Wide-Spread, Low Concentration Perchlorate Impacts to Groundwater -- Stable Isotopic Composition of Chlorine and Oxygen in Synthetic and Natural Perchlorate -- Recent Developments in Perchlorate Detection -- The Ecotoxicology of Perchlorate in the Environment -- Perchlorate Toxicity and Risk Assessment -- Using Biomonitoring to Assess Human Exposure to Perchlorate -- Recent Advances in Ion Exchange for Perchlorate Treatment, Recovery and Destruction -- Field Demonstration using Highly Selective, Regenerable Ion Exchange and Perchlorate Destruction Technologies for Water Treatment -- The Microbiology of Perchlorate Reduction and its Bioremediative Application -- The Biochemistry and Genetics of Microbial Perchlorate Reduction -- Field Demonstration of In Situ Perchlorate Bioremediation in Groundwater -- Perchlorate Removal by Modified Activated Carbon -- Titanium Catalyzed Perchlorate Reduction and Applications -- Membrane and Other Treatment Technologies — Pros and Cons.
Keywords: Water pollution; Ecotoxicology; Water quality; Geochemistry; Microbiology; Environmental management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Ecotoxicology; Water Quality/Water Pollution; Geochemistry; Microbiology; Environmental Management